Lukas Geniušas performs Prokofiev's Piano sonata no. 5 piano recital - Prokofiev, Sergey 1891-1953 (Telmondis, 2017)
Silver medalist of 2015 Tchaikovsky Competition, Lukas Geniušas has been praised for his "agonizing search for a performance style that is fully modern and catching the spirit of the age" (Kommersant Russia). The outstanding young talent performs here Prokofiev's Piano Sonata No. 5 as part of the 2016 MPHIL 360°. For the 2016 MPhil 360° festival, Valery Gergiev and the Münchner Philharmoniker put together a musical celebration of impressive proportions! The three-day festival put a special focus on Sergei Prokofiev's piano sonatas performed by honorees of the International Tchaikovsky competition
Keywords: Sonatas (Piano); Sonatas; Filmed performances; Internet videos